Accounting change in the Scottish and Westminster central governments: A study of voice and legitimation. (9th October 2019) - Hyndman, Noel; Liguori, Mariannuziata
Abstract: Organisational voice processes are crucial during change. These will affect actors' individual understanding of change and the way in which change is perceived and legitimated generally. Looking at accounting changes at two government levels (Westminster and Scotland), this paper explores relationships between organisational voice processes during change (exploring these in terms of horizontal/vertical and promotive/prohibitive dimensions) and legitimation strategies subsequently used by the actors involved. In Westminster, where promotive vertical voicing was particularly identifiable, interviewees predominantly legitimated change through rationalisation strategies. In Scotland, where prohibitive, horizontal voice processes were more evident, authorisation strategies tended to prevail. However, regardless of the content and direction of voice, ultimately, the vast majority of key accounting changes in both Westminster and Scotland were supported (legitimated) by actors.